Neokonservativna opozicija politikam enakosti - Smrdelj, Rok (Družboslovne razprave, 2024)
In the article, we address the emergence of the anti-gender movement in Slovenia. Based on content analysis of studies on the anti-gender movement in Slovenia, the main actors of the movement, their arguments, discourses, action strategies, transnational links with ideologically related foreign movements, and the reasons for their successful mobilisation are discussed. We frame the overview of these topics by considering the thesis of the anti-gender movement’s double “legacy” according to which on one hand the movement’s activities indirectly created a political opportunity for the legalisation of marriage equality and, on the other, reshaped the structure of the public debate on sexual and gender rights via the successful introduction of “gender theory” as a mobilising concept. Through the mentioned thesis, we highlight the complexity of the social effects of the anti-gender movement, which constitutes neo-conservative opposition in the field of equality policies today.
Keywords: abortus; antigendersko gibanje; ideologija spola; istospolni odnosi; Konservativizem; LGBTIQ+; politika enakosti; Slovenija; teorija spola